Search for heavy neutral leptons in decays of W bosons using leptonic and semi-leptonic displaced vertices in s $$ \sqrt{s} $$ = 13 TeV pp collisions with the ATLAS detector - The ATLAS collaboration; G. Aad; E. Aakvaag; B. Abbott; S. Abdelhameed; K. Abeling; N. J. Abicht; S. H. Abidi; M. Aboelela; A. Aboulhorma; H. Abramowicz; Y. Abulaiti; et al. (Journal of High Energy Physics)
Abstract A search is performed for long-lived heavy neutral leptons (HNLs), produced through the decay of a W boson along with a muon or electron. Two channels are explored: a leptonic channel, in which the HNL decays into two leptons and a neutrino, and a semi-leptonic channel, in which the HNL decays into a lepton and a charged pion. The search is performed with 140 fb −1 of s $$ \sqrt{s} $$ = 13 TeV proton-proton collision data collected by ATLAS during Run 2 of the Large Hadron Collider. No excess of events is observed; Dirac-like and Majorana-like HNLs with masses below 14.5 GeV and mixing coefficients as small as 10 −7 are excluded at the 95% confidence level. The results are interpreted under different assumptions on the flavour of the leptons from the HNL decays.